Tinjauan Sosial Ekonomi Pelaku Home Industry : (Studi Kasus Pembuat Gula Aren Di Desa Sialang Kecamatan Bangun Purba) - Nadila Tri Ramadani; Tuti Atika (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Humans have diverse life needs, to fulfill these diverse life needs a person must work, whether working in the formal sector or the informal sector. In order to work in the formal sector a person must have adequate knowledge and skills. Apart from that, job vacancies in the formal sector have employee acceptance limits. This is what causes many people to work in the informal sector to meet their various life needs. One of the jobs included in the informal sector is the home industry. The home industry discussed in this research is the palm sugar making home industry in Sialang Village, Bangun Purba District. The aim of this research is to find out the socio-economic conditions of the home industry owners who make palm sugar in Sialang Village. This research uses a descriptive research method with a qualitative approach with data collection techniques consisting of interviews, observation and literature study. The main informants in this research consisted of 5 owners of palm sugar making home industries in Sialang Village. The research results show that the socio-economic status of the owners of the palm sugar making home industry is unstable because the income obtained from the palm sugar making home industry is very dependent on natural resources. However, home industry owners who make palm sugar feel that the income they earn can fulfill their various life needs.